The impact of artificial intelligence and digital social media on business model innovation: Literature review and mechanism analysis - Hu, Yueyao (Edelweiss Applied Science and Technology, 2026)
Digital technologies (i.e., Artificial Intelligence (AI) and Digital Social Media (DSM)) are key factors driving business model innovation (BMI). Based on Technology Affordances and Constraints (TAC) theory, Resource-based View (RBV) theory, and relevant literature, this paper analyzes the relationship among these factors, their roles, and explores the mediating effect of value integration and the moderating role of strategic alliances. It clarifies the conceptual definitions and dimensions of BMI, AI, DSM, value integration, and strategic alliances. The findings indicate that AI influences BMI by improving decision-making efficiency and optimizing business processes, while DSM promotes innovation and transformation through user interaction and market feedback. Value integration acts as a mediator to facilitate transforming technological resources into innovation value, and strategic alliances enhance technology application effects through resource and risk sharing. This paper reveals the synergistic effects of technology application, resource integration, and alliance collaboration in BMI, providing both theoretical references and practical insights for enterprise digital transformation and BMI.